Software Architecture for Academic Audit Information Management System - Nor Azima, Abu Seman (2010)
The main purpose of this research is to give an understanding of how important is software architecture in a system development process. Software architecture is the second phase in system development life cycle which gave a huge contribution of the system fundamentals that determines the system's remaining development. its deployment and maintenance life. The relationship among requirements, processes, users and results are a never ending relationship where they complete each other and work as a unit. It is much like a framework of ideas, concepts and requirements that are designed before developing and carrying out the actual actions. A comprehensive software architecture which meets the quality standards can be used and referred to for other system's development which also shares the same fundamental concepts. Organization management and governing processes such as auditing management requires a comprehensive and efficient architecture to ensure the auditing processes are done accurately based on the standards set up by the quality control organization. Malaysian Qualifications Agency (MQA) is one of the organizations which monitors and coordinate both the quality assurance and accreditation of national higher learning institute. MQA auditing processes are carried out based on the international quality assurance processes and standards. To ensure the accuracy of auditing processes, the Architecture Tradeoff Analysis Method (ATAM) has been chose as an assessment tool to test the correctness of the architecture.